A hybrid method for fast Monte Carlo simulation of diffuse reflectance from a multi-layered tissue model with tumor-like heterogeneities - Zhu, Caigang (2013)
We present a hybrid method to speed up the Monte Carlo simulation of diffuse reflectance from a multi-layered tissue model with finite-size tumor-like heterogeneities. The proposed method consists of two steps. In the first step, a set of photon trajectory information generated from a baseline Monte Carlo simulation is utilized to scale the exit weight and exit distance of survival photons for the multi-layered tissue model by using a multiple scaling method. In the second step, another set of photon trajectory information including the locations of all collision events from the baseline simulation and the scaling result obtained from the first step are employed by the perturbation Monte Carlo method to estimate diffuse reflectance from the multi-layered tissue model with tumor-like heterogeneities. Our method is demonstrated to be able to shorten simulation time by several orders of magnitude. Moreover, this hybrid method works for a larger range of probe configurations and tumor models compared to the scaling method or the perturbation method alone.